CCDC137 Is a Prognostic Biomarker and Correlates With Immunosuppressive Tumor Microenvironment Based on Pan-Cancer Analysis - Guo, Lihao; Li, Boxin; Lu, Zhaohong; Liang, Hairong; Yang, Hui; Chen, Yuting; Zhu, Shiheng; Zeng, Minjuan; Wei, Yixian; Liu, Tonggong; Jiang, Tikeng; Xuan, Mei; et al. (Frontiers in Molecular Biosciences, 2021)
Background The coiled-coil domain containing (CCDC) family proteins have important biological functions in various diseases. However, the coiled-coil domain containing 137 (CCDC137) was rarely studied. We aim to investigate the role of CCDC137 in pan-cancer. Methods CCDC137 expression was evaluated in RNA sequence expression profilers of pan-cancer and normal tissues from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) database. The influence of CCDC137 on the prognosis of tumor patients was analyzed using clinical survival data from TCGA. Function and pathway enrichment analysis was performed to explore the role of CCDC137 using the R package “clusterProfiler.” We further analyzed the correlation of immune cell infiltration score of TCGA samples and CCDC137 expression using TIMER2 online database. Results CCDC137 was over-expressed and associated with worse survival status in various tumor types. CCDC137 expression was positively correlated with tumor associated macrophages (TAMs) and cancer associated fibroblasts (CAFs) in Lower Grade Glioma (LGG) and Uveal Melanoma (UVM). In addition, high CCDC137 expression was positively correlated with most immunosuppressive genes, including TGFB1, PD-L1, and IL10RB in LGG and UVM. Conclusions Our study identified CCDC137 as an oncogene and predictor of worse survival in most tumor types. High CCDC137 may contribute to elevated infiltration of TAMs and CAFs and be associated with tumor immunosuppressive status.